2018
DOI: 10.4172/2329-6917.1000248
|View full text |Cite
|
Sign up to set email alerts
|

Testicular Relapse in Acute Lymphoblastic Leukemia (ALL): Guidelines Must be Changed

Abstract: Guidelines for the treatment of testicular recurrences need to be changed: a patient with unilateral testicular recurrence of ALL has been unnecessarily castrated by irradiation. The patient has been free of disease for 12 years, having had chemotherapy, several bone marrow transplants and left Orchyepididimectomy. Nevertheless, due to irradiation of the right testicle, he has been left permanently under hormonal replacement and with unavoidable infertility. This outcome could have been avoided if treatment gu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(6 citation statements)
references
References 8 publications
0
6
0
Order By: Relevance
“…The suspect arises in children treated for ALL who present enlarged testis. The confirmation of diagnosis can be obtained through a fine needle aspiration (FNA) biopsy, both of the affected testis and the contralateral, and the treatment is based on the orchiectomy or on radiation therapy (RT), both causing castration [ 29 ].…”
Section: Scrotal Massmentioning
confidence: 99%
“…The suspect arises in children treated for ALL who present enlarged testis. The confirmation of diagnosis can be obtained through a fine needle aspiration (FNA) biopsy, both of the affected testis and the contralateral, and the treatment is based on the orchiectomy or on radiation therapy (RT), both causing castration [ 29 ].…”
Section: Scrotal Massmentioning
confidence: 99%
“…The testes have long been considered a sanctuary site for leukemic cells [6]. Testicular relapses in acute lymphoblastic leukaemia, tends to account for a major proportion of the poor outcome of disease in boys compared with girls.…”
Section: Discussionmentioning
confidence: 99%
“…Leukemic cells are able to infiltrate various extramedullary tissues during the disease process [5]. Studies have showed that testis is a sanctuary site [6,7] Testicular infiltration more commonly occurs later during the course of disease and at relapse [7]. Initial presentation with primarily testicular disease is exceedingly rare [8,9].…”
Section: Introductionmentioning
confidence: 99%
“…Three publicly available cancer images datasets are used in this paper, including (1) LUNA16 [40] with X-ray images for lung nodule classification, (2) the Kaggle (CE-MRI) [41] dataset with MRI high contrast-colored images, and (3) the Acute Lymphoblastic Leukemia (ALL) [42] dataset with microscopic images. To verify that the proposed adversary defense model described in the previous section is generally appropriate for the AI-based cancer classification domain.…”
Section: Datasets Characteristicsmentioning
confidence: 99%
“…Acute Lymphoblastic Leukemia (ALL) [42]: This dataset is used to classify and identify ALL blasts in the most common cancer type of childhood and is publicly available at the Kaggle website. This dataset contains 3256 PBS images from 89 patients collected in the bone marrow laboratory of Taleqani Hospital (Tehran, Iran).…”
Section: Datasets Characteristicsmentioning
confidence: 99%